2010
DOI: 10.1364/oe.18.010462
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic deformation of red blood cell
in Dual-trap Optical Tweezers

Abstract: Three-dimensional dynamic deformation of a red blood cell in a dual-trap optical tweezers is computed with the elastic membrane theory and is compared with the experimental results. When a soft particle is trapped by a laser beam, the particle is deformed depending on the radiation stress distribution whereas the stress distribution on the particle in turn depends on the deformation of its morphological shape. We compute the stress re-distribution on the deformed cell and its subsequent deformations recursivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 13 publications
1
56
0
Order By: Relevance
“…[45; 46] In our work, however, and similar to Rancourt-Grenier et al [47]), we trap the RBC -orientation as shown in the inset of Figure 2. All tested RBCs were subject to the same protocol for stretching, achieved by slowly increasing the separation between the beam foci before releasing and allowing the cell to relax back to its natural length.…”
Section: Rbc Deformabilitysupporting
confidence: 60%
“…[45; 46] In our work, however, and similar to Rancourt-Grenier et al [47]), we trap the RBC -orientation as shown in the inset of Figure 2. All tested RBCs were subject to the same protocol for stretching, achieved by slowly increasing the separation between the beam foci before releasing and allowing the cell to relax back to its natural length.…”
Section: Rbc Deformabilitysupporting
confidence: 60%
“…Further, TFPs, with the features of ease in fabrication and very small sizes, provide a much more compact configuration than do the bulky optical systems consisting of a series of objectives. Recent studies have also demonstrated that the RBCs can be stretched using two cleaved optical fiber, which is called an optical stretcher [25,28]. Compared to the optical stretcher, the parabolic shape of the TFP tips provides a stronger focusing effect for outputted laser beams.…”
Section: Resultsmentioning
confidence: 99%
“…Motivating integration within microfluidic devices are the comparable pN hydrodynamic forces, the relative length scales, the ease of use and fabrication, the biocompatibility, and the low cost [4]. Because of this, microfluidics and optical forces have been combined to create optical stretchers [5][6][7] which impart stresses on the surface of deformable microscale objects [5][6][7][8][9][10][11][12], an approach that has seen significant recent interest because of the non-invasive nature of optical traps and the desire to measure cell mechanical properties [13,14]. Currently, the simplest linear optical stretcher employs a single inexpensive, high-power diode laser bar source [15][16][17] to stretch cells along the laser long axis [18][19][20].…”
Section: Introductionmentioning
confidence: 99%